Infrastructures for online social networking services [guest editorial] - Datta, Anwitaman (2013)
The rapid proliferation of social media, online communities, and collectively produced knowledge resources has accelerated the convergence of technological and social networks, resulting in a dynamic ecosystem of online social networking services, environments, and applications. The proliferation of online social networks (OSNs) has had a profound impact on the Internet, reshaping its structure, design, and utility. Despite this success, however, the research community must address significant challenges to enable further development of these services, including the development, deployment, management, and operation of scalable, secure, and interoperable OSN infrastructures.